Prevalence of congenital anomalies of the upper limbs in Brazil: a descriptive cross-sectional study - Moura, Samuel Ricardo Batista; Nakachima, Luis Renato; Santos, João Baptista Gomes dos; Belloti, João Carlos; Fernandes, Carlos Henrique; Faloppa, Flavio; Moraes, Vinicius Ynoe de; Sabongi, Rodrigo Guerra (São Paulo Medical Journal, 2025)
BACKGROUND: Congenital Anomalies of the Upper Limb (CAUL) are a group of structural or functional abnormalities that develop during intrauterine life and can lead to limb dysfunction. OBJECTIVES: To analyze the prevalence of congenital anomalies of the upper limbs in Brazil and assess maternal and neonatal variables. DESIGN AND SETTING: A cross-sectional, descriptive study was conducted on congenital upper limb malformations among live births across Brazil. METHODS: The study spanned from 2010 to 2019. Data were sourced from the Department of Informatics of the Unified Health System (DATASUS) and the Live Birth Information System (SINASC) portal. Analyses focused on the information reported in field 41 of the Live Birth Declaration Form entered into the computerized system. RESULTS: The most common anomaly in Brazil was supernumerary fingers, classified as ICD-Q69.0, affecting 11,708 children, with a prevalence of 4.02 per 10,000 live births. Mothers aged over 40 years had a 36% higher prevalence of having children with CAUL than mothers under 40 years old (OR = 1.36; 95% CI 1.19-1.56). Newborns weighing ≤ 2,499 g were 2.64 times more likely to have CAUL compared to those weighing ≥ 2,500 g (OR = 2.64; 95% CI 2.55-2.73). CONCLUSION: There was an observed increase in the reporting of CAUL cases over the decade studied. This trend serves as an alert for health agencies, as understanding the prevalence of CAUL and its associated factors is crucial for preventive medicine.